Gambaran Pendampingan Pengobatan ISPA (Infeksi Saluran Pernapasan Akut) Non Pneumonia oleh Tenaga Kesehatan di Puskesmas Cilacap Selatan II - Melati Aprilliana Ramadhani; Elisa Issusilaningtyas (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2019)
Acute Respiratory Infection (ARI) is a disease of the upper or lower respiratory tract, usually contagious and can causes a variety of spectrums of diseases ranging from mild infections to severe and deadly diseases. ARI is divided into 3 classifications of cases are pneumonia, severe pneumonia, and non pneumonia. The prevalence of ARI in Indonesia is 25%. ARI causes high mortality of baby and toddlers, which is about 1 in 4 deaths. Drug used in patients with ARI was very influential the success of healing the rate of the disease. This study aims to determine the pattern of drug use in non-pneumonia ARI patients in toddlers and children, and evaluate the DRPs in outpatient installations in Cilacap Selatan II Health Center in February 2018. This study is an observational study whose results are presented in evaluative descriptions with restrospectively data collection based on medical record data for toddlers and children non-pneumonia ARI patients. The results showed that the pattern of non-pneumonia ARI use in toddlers and children in the outpatient installation of Cilacap Selatan II Health Center was supportive therapy by 100% without antibiotics therapy, so it could be concluded that the drug selection was given to toddlers and children in The outpatient installation of Cilacap Selatan Health Center II is right.